Forgiveness, gratitude, and the flourishing of emerging adults with divorced parents - Tessy, Nastasya Ryoko Bonang; Setiasih, Setiasih; Nanik, Nanik (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
Parental divorce affects the ability of individuals to flourish. This study aims to determine the relationship between forgiveness and gratitude and the flourishing of emerging adults whose parents have divorced. Voluntary convenience sampling was used to identify respondents (N = 429 emerging adults whose parents had been divorced for at least two years). Data were collected using the Emotional Forgiveness Scale, the Gratitude Questionnaire-Six Item Form, and the PERMA Profiler. Data analysis was performed using multiple regression analysis. The results show that forgiveness and gratitude were significantly associated with flourishing in emerging adults whose parents divorced (R2 = .382, F = 131.634, p < .05). The contribution of gratitude (β = 1.299) to flourishing was greater than that of forgiveness (β = .722). Forgiveness and gratitude can predict flourishing in emerging adults whose parents are divorced, in this case, the role of gratitude is greater than forgiveness. Interventions that combine the basis of forgiveness and gratitude can be used to optimize the flourishing of such emerging adults whose parents are divorced.